Sistem Evaluasi Bahan Pembelajaran Menggunakan Metode DEMATEL dan ANP - Permadi, Ginanjar Setyo; Vitadiar, Tanhella Zein; Kistofer, Terdy (Universitas Diponegoro, 2019)
Evaluation of learning that will be given or is being given to diagnose success and failure in understanding teaching material. The failure to provide learning can be caused by the use of teaching methods or inappropriate media, and the delivery language that is difficult to understand. By applying information technology in evaluating learning materials, an evaluation system can be developed to assess and improve the quality of learning materials with certain criteria. So the problem of failure in the learning process can be known based on the learning material used. This study uses the DEMATEL and ANP methods as a basis for decision making by evaluating lecturer learning materials with a sample of 12 teachers. The DEMATEL method helps process data which is then forwarded by the ANP method in identifying interdependent relationships between criteria. With the use of the DEMATEL and ANP methods, it is expected to be able to assist in evaluating learning materials with the aim of always trying to provide good learning material based on factors or criteria that should be. The results of the study obtained a pair-level matrix Consistency Ratio (CR) value of 0.0661. Furthermore, calculating alternative ranking weights can be seen in Table 5. Furthermore, the results of the evaluation are used as further improvement efforts and to find out where there are unsuccessful outcomes in learning. Thus can be continuous between the objectives and the final results of teaching